All-solid-state battery and method for manufacturing an all-solid-state battery
Patent Information
- Application Number
- JP2025059231
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0032】 本発明によれば、耐久性を向上可能な全固体電池を提供することができる。
Smart Images

Figure 2026166352000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an all-solid-state battery and a method for manufacturing the all-solid-state battery.
Background Art
[0002] In recent years, research and development on secondary batteries that contribute to energy efficiency have been carried out to ensure that more people can access affordable, reliable, sustainable and advanced energy.
[0003] Among secondary batteries, all-solid-state batteries using a solid electrolyte as the electrolyte are particularly attracting attention, as they are superior in terms of high safety due to the non-flammable nature of the solid electrolyte and having a higher energy density. As all-solid-state batteries, all-solid-state batteries having a laminated structure in which a plurality of positive electrode layers and negative electrode layers are alternately laminated via solid electrolyte layers have been studied (for example, Patent Document 1).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problems to be Solved by the Invention
[0005] In all-solid-state batteries, current collecting tabs extending from current collectors are bundled. All-solid-state batteries expand or contract as they are charged and discharged. In the all-solid-state battery of Patent Document 1, the current collecting tabs (current collectors) are in a pulled state when the all-solid-state battery expands. When charge and discharge of the all-solid-state battery are repeated, the current collectors are repeatedly pulled, and may eventually break.
[0006] An object of the present invention is to provide an all-solid-state battery capable of improving durability and a method for manufacturing the all-solid-state battery.
Means for Solving the Problems
[0007] (1) The present invention relates to an all-solid-state battery in which a negative electrode layer and a positive electrode layer having a positive electrode active material layer and a positive electrode current collector layer are laminated via a solid electrolyte layer, wherein the direction of lamination is defined as the lamination direction, and one of the directions perpendicular to the lamination direction is defined as the first direction, the positive electrode current collector layer has a positive electrode current collector layer main body that overlaps with the positive electrode active material layer in the lamination direction, and a positive electrode tab extending from the positive electrode current collector layer main body to one side in the first direction, the positive electrode current collector layer is a polycrystalline material, and in the first region including the boundary between the positive electrode tab and the positive electrode current collector layer main body, the average particle size of the polycrystalline material is larger than the average particle size of the polycrystalline material in the positive electrode current collector layer main body, and the average particle size of the polycrystalline material in the first region is less than 3.0 μm.
[0008] Among the various parts of the positive electrode current collector layer, the region near the base of the positive electrode tab is considered to be prone to fracture because it is easily affected by the expansion and contraction of the all-solid-state battery. According to the all-solid-state battery described in (1), by forming a first region in the region near the base of the positive electrode tab, in which the average particle size of the polycrystalline material is relatively large, the strength of the region near the base of the positive electrode tab can be improved. Furthermore, by having an average particle size of the polycrystalline material in the first region of less than 3.0 μm, sufficient flexibility of the positive electrode tab can be ensured. As a result, fracture of the positive electrode current collector layer can be suppressed. Therefore, an all-solid-state battery with excellent durability can be provided.
[0009] Furthermore, if the average particle size of the polycrystalline material in the positive electrode current collector layer increases, the electrical resistance in the positive electrode current collector layer increases, which may impair the battery performance of the all-solid-state battery. According to the all-solid-state battery described in (1), the increase in electrical resistance in the main body of the positive electrode current collector layer can be suppressed by reducing the average particle size of the polycrystalline material in the main body of the positive electrode current collector layer.
[0010] Furthermore, since the positive electrode current collector layer is laminated with other layers, its strength is relatively less of a problem. Therefore, it is possible to improve the durability of the all-solid-state battery while ensuring its battery performance.
[0011] Furthermore, by having an average particle size of less than 3.0 μm in the first region, the increase in electrical resistance in the first region can be suppressed. This allows for more effectively suppression of the degradation of the battery performance of the all-solid-state battery.
[0012] (2) In the all-solid-state battery described in (1) above, the positive electrode current collector layer may consist of at least one of aluminum and an aluminum alloy.
[0013] In the all-solid-state battery described in (2), since aluminum particles grow easily when heated, the first region can be suitably formed by heating the positive electrode current collector layer.
[0014] Furthermore, because aluminum has excellent corrosion resistance, it makes it easier to ensure the durability of the positive electrode current collector layer over the long term.
[0015] (3) In the all-solid-state battery described in (1) or (2) above, the average particle size of the polycrystalline material in the second region of the positive electrode tab that is on the opposite side from the positive electrode current collector layer body portion than the first region may be smaller than the average particle size of the polycrystalline material in the first region.
[0016] Since the positive electrode tab is joined to other positive electrode tabs in a bent state, it is preferable that it be somewhat flexible. In particular, it is preferable that the region near the tip of the positive electrode tab be flexible. On the other hand, if the average grain size of the polycrystalline material of the positive electrode tab is increased, the positive electrode current collector layer becomes rigid, which may cause the positive electrode tab to buckle when the all-solid-state battery expands. However, according to the all-solid-state battery described in (3), the flexibility of the positive electrode tab can be easily ensured by reducing the average grain size of the polycrystalline material in the second region near the tip of the positive electrode tab. In particular, it is easier to ensure flexibility near the tip of the positive electrode tab. This makes it possible to suppress buckling of the positive electrode current collector layer.
[0017] (4) In the all-solid-state battery described in any one of (1) to (3) above, the end of the first region opposite to the positive electrode current collector layer body portion may be on the positive electrode current collector layer body portion side than the central portion of the positive electrode tab in the first direction.
[0018] According to the all-solid-state battery described in (4), the region in the positive electrode current collector layer that is formed relatively hard can be extended further toward the tip, thereby effectively suppressing fracture of the positive electrode current collector layer. Furthermore, by adjusting the position in the first direction of the end of the first region opposite to the main body of the positive electrode current collector layer, the balance between the effect of suppressing fracture of the positive electrode current collector layer and the effect of suppressing buckling of the positive electrode current collector layer can be adjusted.
[0019] (5) In the all-solid-state battery described in any one of (1) to (4) above, the average particle size of the polycrystalline material in the first region may be 0.5 μm or more and less than 3.0 μm.
[0020] According to the all-solid-state battery described in (5), by increasing the average grain size of the polycrystalline material in the first region to a certain extent, it is possible to ensure the strength of the first region, thereby suppressing buckling of the positive electrode tab. By decreasing the average grain size of the polycrystalline material within the first region to a certain extent, it is possible to ensure the flexibility of the first region, thereby suppressing fracture of the positive electrode tab. Therefore, the durability of the all-solid-state battery can be more favorably improved.
[0021] (6) In the all-solid-state battery described in any one of (1) to (5) above, the thickness of the positive electrode current collector layer may be 0.005 mm or more and 0.05 mm or less.
[0022] If the thickness of the positive electrode current collector layer is insufficient, the strength of the positive electrode current collector layer will be inadequate. If the thickness of the positive electrode current collector layer is excessive, excessive electrical resistance will occur in the positive electrode current collector layer. However, with the all-solid-state battery described in (6), it is possible to more preferably improve the durability of the all-solid-state battery while ensuring its battery performance.
[0023] (7) In the all-solid-state battery according to any one of the above (1) to (6), the positive electrode active material layer may contain a lithium-nickel-cobalt-manganese composite oxide.
[0024] According to the all-solid-state battery described in (7), the thermal durability of the positive electrode active material layer can be improved, so that the positive electrode current collector layer and the positive electrode active material layer can be easily heated at the same time.
[0025] Further, the positive electrode active material layer containing the lithium-nickel-cobalt-manganese composite oxide can shrink during charging of the all-solid-state battery. Thereby, expansion of the all-solid-state battery during charging can be suppressed, so that breakage of the positive electrode current collector layer can be suppressed.
[0026] (8) The present invention is the method for manufacturing an all-solid-state battery according to the above (1), comprising: preparing a positive electrode current collector layer raw material which is a polycrystalline body and has a positive electrode current collector layer main body portion on which the positive electrode active material layer is disposed, and a positive electrode tab extending from the positive electrode current collector layer main body portion; and a grain growth step of heating a boundary portion of the positive electrode tab with the positive electrode current collector layer main body portion to form a first region where the average grain size of the polycrystalline body is larger than the average grain size of the polycrystalline body in the positive electrode current collector layer main body portion. This is a method for manufacturing an all-solid-state battery.
[0027] By heating the positive electrode current collector layer, the crystal grains G forming the polycrystalline body of the positive electrode current collector layer can be grown. According to the method for manufacturing an all-solid-state battery described in (8), by performing the grain growth step, the crystal grains forming the polycrystalline body can be grown in the region near the boundary portion of the positive electrode tab with the positive electrode current collector layer main body portion, so that the first region can be formed in the positive electrode current collector layer.
[0028] (9) In the method for manufacturing an all-solid-state battery according to the above (8), the method may include an integrated pressing step of stacking and pressing the positive electrode layer, the negative electrode layer, and the solid electrolyte layer, and the grain growth step may be performed before the integrated pressing step.
[0029] When the positive electrode current collector layer is pressed, it becomes difficult for the crystal particles within the positive electrode current collector layer to grow. However, according to the method for manufacturing an all-solid-state battery described in (9), the crystal particles within the positive electrode current collector layer can be grown suitably, making it easier to create a difference between the average particle size of the polycrystalline material in the first region and the average particle size of the polycrystalline material in the region of the positive electrode current collector layer excluding the first region.
[0030] (10) In the all-solid-state battery described in (9) above, a positive electrode pressing step is provided in which the positive electrode active material layer and the positive electrode current collector layer are stacked and pressed together, and the grain growth step may be performed before the positive electrode pressing step.
[0031] According to the method for manufacturing an all-solid-state battery described in (10), the crystal particles in the positive electrode current collector layer can be grown more favorably, making it easier to differentiate between the average particle size of the polycrystalline material in the first region and the average particle size of the polycrystalline material in the region of the positive electrode current collector layer excluding the first region. [Effects of the Invention]
[0032] According to the present invention, it is possible to provide an all-solid-state battery with improved durability.
[0033] According to the present invention, it is possible to provide a method for manufacturing an all-solid-state battery that can improve durability. [Brief explanation of the drawing]
[0034] [Figure 1] This is a perspective view of the external appearance of the all-solid-state battery according to the embodiment. [Figure 2] This is a cross-sectional view of an all-solid-state battery along the line II-II in Figure 1. [Figure 3] This is a cross-sectional view of an all-solid-state battery along the line III-III in Figure 1. [Figure 4] This is a disassembled perspective view of an all-solid-state battery. [Figure 5] This is a plan view of the positive electrode layer as seen in the stacking direction. [Figure 6] This is a cross-sectional view along the line VI-VI in Figure 5. [Figure 7] This is an enlarged view of section VII in Figure 6. [Figure 8] This is an enlarged view of section VIII in Figure 6. [Figure 9] This is a process diagram showing a method for manufacturing an all-solid-state battery according to the embodiment. [Modes for carrying out the invention]
[0035] The following describes an embodiment of the all-solid-state battery 1 of the present invention. The type of all-solid-state battery 1 is not particularly limited, but for example, it is an all-solid-state lithium battery that uses lithium ions as a charge transfer medium. As shown in Figures 1 to 4, the all-solid-state battery 1 has a structure in which a positive electrode layer 20 and a negative electrode layer 10 are stacked via a solid electrolyte layer 30.
[0036] In this specification, the direction in which the positive electrode layer 20 and the negative electrode layer 10 are stacked via the solid electrolyte layer 30 is defined as the "T direction". The T direction corresponds to the stacking direction. One of the directions perpendicular to the T direction is defined as the "X direction". The X direction corresponds to the first direction. The directions perpendicular to both the T direction and the X direction are defined as the "Y direction". The Y direction corresponds to the second direction. One side of the T direction is defined as the "T+ direction", and the opposite side of the T+ direction is defined as the "T- direction". One side of the X direction is defined as the "X+ direction", and the opposite side of the X+ direction is defined as the "X- direction". One side of the Y direction is defined as the "Y+ direction", and the opposite side of the Y+ direction is defined as the "Y- direction".
[0037] (All-solid-state battery) The all-solid-state battery 1 comprises, for example, a plurality of negative electrode layers 10, a plurality of solid electrolyte layers 30, and a plurality of positive electrode layers 20. The negative electrode layers 10, solid electrolyte layers 30, positive electrode layers 20, and solid electrolyte layers 30 are stacked in this order. The total number of stacked negative electrode layers 10 and positive electrode layers 20 is not particularly limited, but is preferably 10 or more. Note that in Figures 2 to 4, the vicinity of each end in the T direction of the all-solid-state battery 1 is omitted from the illustration.
[0038] The all-solid-state battery 1 comprises an outer casing 5, a negative electrode tab lead 6, and a positive electrode tab lead 7. The outer casing 5 is provided on the surface of the all-solid-state battery 1. The outer casing 5 covers a laminate of a negative electrode layer 10, a solid electrolyte layer 30, and a positive electrode layer 20. The outer casing 5 is formed of, for example, resin. In Figure 1, the outer casing 5 is shown by a dashed line. The negative electrode tab lead 6 is connected to a bundled negative electrode tab 14 (described later). The negative electrode tab lead 6 is drawn out from the outer casing 5. The positive electrode tab lead 7 is connected to a bundled positive electrode tab 24 (described later). The positive electrode tab lead 7 is drawn out from the outer casing 5.
[0039] (Negative electrode layer) The negative electrode layer 10 includes a negative electrode active material layer 15 and a negative electrode current collector layer 11. One negative electrode layer 10 includes, for example, one negative electrode current collector layer 11 and two negative electrode active material layers 15 provided sandwiching the negative electrode current collector layer 11 in the T direction.
[0040] The negative electrode active material layer 15 contains a negative electrode active material. Examples of negative electrode active materials include lithium metal, lithium alloy, silicon (Si), silicon alloys and other silicon-based active materials, lithium titanate (Li4Ti5O 12 Examples include lithium transition metal oxides such as ), transition metal oxides such as TiO2, Nb2O3 and WO3, metal sulfides, metal nitrides, carbon materials such as graphite, soft carbon and hard carbon, and metallic indium. The negative electrode active material layer 15 is preferably composed of lithium metal. The negative electrode active material layer 15 may further contain a solid electrolyte, a conductive additive, a binder, etc.
[0041] The negative electrode active material layer 15 has a shape that is, for example, a flat plate with its surface extending along the X and Y directions. The shape of the negative electrode active material layer 15 when viewed in the T direction is, for example, a rectangular shape with its longer side extending along the X direction.
[0042] The negative electrode current collector layer 11 is provided adjacent to the negative electrode active material layer 15. The negative electrode current collector layer 11 is not particularly limited, but is made of copper, for example. The shape of the negative electrode current collector layer 11 is, for example, foil-like. The negative electrode current collector layer 11 has a negative electrode current collector layer body portion 12 and a negative electrode tab 14.
[0043] The negative electrode current collector layer main body 12 is the portion of the negative electrode current collector layer 11 that overlaps with the adjacent negative electrode active material layer 15 in the T direction. The shape of the negative electrode current collector layer main body 12 in view in the T direction is, for example, a roughly rectangular shape with its long side extending along the X direction.
[0044] The negative electrode tab 14 is a portion of the negative electrode current collector layer 11 that extends from the negative electrode current collector layer main body 12 in a predetermined direction. For example, the negative electrode tab 14 extends from the negative electrode current collector layer main body 12 to one side in the L direction (more specifically, the L- direction). The Y-direction dimension of the negative electrode tab 14 is smaller than the Y-direction dimension of the negative electrode current collector layer main body 12. The shape of the negative electrode tab 14 in a T-direction view is, for example, a roughly rectangular shape with its long side extending along the X direction. The tips of multiple negative electrode tabs 14 are converged to one another.
[0045] (Solid electrolyte layer) The solid electrolyte layer 30 is provided between the negative electrode layer 10 and the positive electrode layer 20. The solid electrolyte layer 30 contains a solid electrolyte material. Examples of solid electrolyte materials include sulfide solid electrolyte materials and oxide solid electrolyte materials.
[0046] (Positive electrode layer) The positive electrode layer 20 includes a positive electrode active material layer 25 and a positive electrode current collector layer 21. One positive electrode layer 20 includes, for example, one positive electrode current collector layer 21 and two positive electrode active material layers 25 provided sandwiching the positive electrode current collector layer 21 in the T direction.
[0047] The positive electrode active material layer 25 contains a positive electrode active material. Examples of positive electrode active materials include transition metal chalcogenides such as titanium disulfide, molybdenum disulfide, and niobium selenide, and transition metal oxides such as lithium nickelate (LiNiO2), lithium manganeseate (LiMnO2, LiMn2O4), and lithium cobaltate (LiCoO2). The positive electrode active material layer 25 may further contain a solid electrolyte, a conductive additive, a binder, and the like.
[0048] The positive electrode active material layer 25 has a shape that is, for example, a flat plate with its surface extending along the X and Y directions. The shape of the positive electrode active material layer 25 when viewed in the T direction is, for example, a rectangular shape with its longer side extending along the X direction.
[0049] An insulating frame 26, for example, is provided on the outer periphery of the positive electrode active material layer 25.
[0050] The insulating frame 26 contains an electronically insulating material. Examples of electronically insulating materials include insulating oxides such as alumina, resins such as polyvinylidene fluoride (PVDF), and rubbers such as styrene-butadiene rubber (SBR). The insulating frame 26 is preferably formed of alumina. The insulating frame 26 may also have ionic conductivity.
[0051] The insulating frame 26 has a substantially flat shape with its surface extending along the X and Y directions. The shape of the insulating frame 26 when viewed in the T direction is, for example, a substantially rectangular frame shape with its longer side extending along the X direction.
[0052] The insulating frame 26 can suppress short circuits in the all-solid-state battery 1 and improve the strength of the all-solid-state battery 1.
[0053] The positive electrode current collector layer 21 is provided adjacent to the positive electrode active material layer 25. The positive electrode current collector layer 21 is formed of a current collector. Examples of current collectors include aluminum, copper, nickel, vanadium, iron, titanium, stainless steel, gold, platinum, and carbon. The positive electrode current collector layer 21 is formed of aluminum, for example. The shape of the positive electrode current collector layer 21 is, for example, foil-like. The positive electrode current collector layer 21 has a positive electrode current collector layer body portion 22 and a positive electrode tab 24.
[0054] The positive electrode current collector layer body portion 22 is the portion of the positive electrode current collector layer 21 that overlaps with the positive electrode active material layer 25 adjacent to the positive electrode current collector layer 21 in the T direction, and more specifically, it is the portion that overlaps with at least one of the two positive electrode active material layers 25 adjacent to the positive electrode current collector layer 21 in the T direction. The shape of the positive electrode current collector layer body portion 22 in view in the T direction is, for example, a rectangle with its long side extending along the X direction.
[0055] Furthermore, if an insulating frame 26 is provided on the positive electrode active material layer 25, "the portion of the positive electrode current collector layer 21 that overlaps in the T direction with the positive electrode active material layer 25 adjacent to the positive electrode current collector layer 21" means the portion of the positive electrode current collector layer 21 that overlaps in the T direction with at least one of the following: the positive electrode active material layer 25 adjacent to the positive electrode current collector layer 21, and the insulating frame 26 provided on the outer periphery of the positive electrode active material layer 25.
[0056] The positive electrode tab 24 is a portion of the positive electrode current collector layer 21 that extends from the positive electrode current collector layer main body 22 in a predetermined direction. For example, the positive electrode tab 24 extends from the positive electrode current collector layer main body 22 to one side in the X direction (more specifically, the X+ direction). The Y-direction dimension of the positive electrode tab 24 is smaller than the Y-direction dimension of the positive electrode current collector layer main body 22. The shape of the positive electrode tab 24 in a T-direction view is, for example, a roughly rectangular shape with its long side extending along the X direction. The tips of multiple positive electrode tabs 24 are converged to one another.
[0057] (Middle class) Furthermore, the all-solid-state battery 1 includes, for example, a plurality of intermediate layers 40 provided between adjacent negative electrode layers 10 and solid electrolyte layers 30.
[0058] The intermediate layer 40 includes, for example, a metal that can be alloyed with lithium and carbon. Examples of metals that can be alloyed with lithium include Mg, Zn, Al, In, Si, Ge, Sn, Ag, Au, Pt, Pd, Pb, Sb, and Bi. The shape of the intermediate layer 40 is, for example, a substantially rectangular plate with plate surfaces extending in the X and Y directions.
[0059] Since the intermediate layer 40 is formed to be more flexible than the negative electrode layer 10 and the solid electrolyte layer 30, it is easier for it to adhere to the negative electrode layer 10 and the solid electrolyte layer 30. The intermediate layer 40 helps to suppress delamination between the negative electrode layer 10 and the solid electrolyte layer 30.
[0060] Here, the positive electrode current collector layer 21 is a polycrystalline material (see Figures 7 and 8). The individual crystal grains that form the polycrystalline material are referred to as "crystal grains G".
[0061] As shown in Figures 5, 6, and 8, in the first region R1, which includes the boundary between the positive electrode tab 24 and the positive electrode current collector layer main body 22, the average grain size of the polycrystalline material is larger than the average grain size of the polycrystalline material in the positive electrode current collector layer main body 22. Within the region of the positive electrode current collector layer main body 22 closer to the first region R1, the grain size of the crystalline grains G decreases, for example, as the distance from the first region R1 increases.
[0062] Figure 5 is a plan view of the positive electrode layer 20, viewed from the T+ direction towards the T- direction. For the sake of explanation, the positive electrode current collector layer 21 located on the T+ direction side of the positive electrode current collector layer 21 is omitted from the illustration in Figure 5.
[0063] In this specification, the cross-section of the positive electrode current collector layer 21 that passes through the center of the positive electrode tab 24 in the Y direction and extends parallel to the T and X directions is defined as the "reference cross-section". Figure 6 shows the reference cross-section. "Particle size of the polycrystalline material" means the equivalent circular diameter of the crystal grains G constituting the polycrystalline material. "Average particle size of the polycrystalline material in a region" means the D50 of the crystal grains G within that region in the reference cross-section.
[0064] The particle size of the crystal grains G within the positive electrode current collector layer 21 is measured by observing a reference cross-section with a scanning electron microscope (SEM).
[0065] The positive electrode current collector layer 21 is preferably made of at least one of aluminum and an aluminum alloy. The crystalline particles G are, for example, aluminum particles.
[0066] As shown in Figures 5, 6, and 7, it is preferable that the average grain size of the polycrystalline material in the second region R2 (sometimes referred to as "tab-side second region R21"), which is located on the opposite side (X+ direction side) from the positive electrode current collector layer body 22 side to the first region R1 of the positive electrode tab 24, is smaller than the average grain size of the polycrystalline material in the first region R1. Within the region of the tab-side second region R21 closer to the positive electrode tab 24, the grain size of the crystal grains G decreases, for example, as the distance from the first region R1 increases.
[0067] The end of the first region R1 opposite to the positive electrode current collector layer main body 22 (X+ side) is located, for example, near the center of the positive electrode tab 24 in the X direction. The end of the first region R1 opposite to the positive electrode current collector layer main body 22 (X+ side) may be located further towards the positive electrode current collector layer main body 22 (X- side) than the center of the positive electrode tab 24 in the X direction.
[0068] In this specification, "the central part of the positive electrode tab 24 in the X direction" means the portion of the positive electrode tab 24 that overlaps with a hypothetical straight line drawn parallel to the Y direction, passing through the central part of the X direction between the X+ side end of the positive electrode tab 24 and the X- side end of the positive electrode tab 24.
[0069] Of the positive electrode current collector layer 21, the region on the opposite side (X-direction side) from the tab-side second region R21 side to the first region R1 is defined as the "main body side second region R22". The tab-side second region R21 and the main body side second region R22 are collectively defined as the "second region R2". The average grain size of the polycrystalline material in the first region R1 is, for example, larger than the average grain size of the polycrystalline material in the second region R2.
[0070] The tab-side end of the first region R1 opposite to the second region R21 (X-side) is located, for example, at the boundary between the positive electrode tab 24 and the positive electrode current collector layer main body 22. The tab-side end of the first region R1 opposite to the second region R21 (X-side) may also be located in the middle of the positive electrode current collector layer main body 22 in the X direction.
[0071] The average grain size of the polycrystalline material in the first region R1 is less than 3.0 μm, preferably between 0.5 μm and 3.0 μm. The average grain size of the polycrystalline material in the positive electrode current collector layer 21 is preferably between 0.1 μm and 0.5 μm. The average grain size of the polycrystalline material in the second region R22 on the main body side is preferably between 0.2 μm and 0.5 μm.
[0072] The thickness of the positive electrode current collector layer 21 is preferably 0.005 mm or more and 0.05 mm or less.
[0073] In this specification, "thickness of the positive electrode current collector layer" means the T-direction dimension of the positive electrode current collector layer. More specifically, the thickness of the positive electrode current collector layer is the average value obtained by measuring the T-direction dimension of the positive electrode current collector layer at each intersection of a straight line extending parallel to the X-direction and passing through the center of the positive electrode current collector layer in the Y-direction, and four straight lines extending parallel to the Y-direction that divide the positive electrode current collector layer into five equal parts in the X-direction.
[0074] The positive electrode active material layer 25 preferably contains a lithium nickel cobalt manganese composite oxide.
[0075] (Manufacturing method for all-solid-state batteries) Next, the manufacturing method of the all-solid-state battery 1 according to this embodiment will be described with reference to Figure 9.
[0076] As shown in Figure 9, first, a positive electrode current collector layer raw material is prepared, which is a polycrystalline material having a positive electrode current collector layer main body portion 22 on which the positive electrode active material layer 25 is arranged, and a positive electrode tab 24 extending from the positive electrode current collector layer main body portion 22. For example, aluminum foil is prepared, and the ends of the aluminum foil are cut to form the positive electrode tab 24 (positive electrode tab formation step S11).
[0077] Next, the boundary between the positive electrode tab 24 and the positive electrode current collector layer main body 22 is heated to form a first region in which the average grain size of the polycrystalline material is larger than the average grain size of the polycrystalline material in the positive electrode current collector layer main body 22 (grain growth step S12). In grain growth step S12, a mid-infrared heating device is used to heat the boundary between the positive electrode tab 24 and the positive electrode current collector layer main body 22 within a predetermined temperature range for a predetermined heating time.
[0078] In the grain growth step S12, the temperature when heating the region that will become the first region R1 is, for example, between 150°C and 420°C. In the grain growth step S12, the heating time when heating the region that will become the first region R1 is, for example, between 1 minute and 500 minutes. This allows the crystal grains G within the region that will become the first region R1 to grow.
[0079] In addition, during the grain growth process S12, the region that will become the first region R1 and the region that will become the second region R2 may be heated. In this case, the temperature when heating the region that will become the first region R1 is higher than the temperature when heating the region that will become the second region R2, or the heating time when heating the region that will become the first region R1 is longer than the heating time when heating the region that will become the second region R2, or at least one of these two conditions. The temperature when heating the region that will become the second region R2 is, for example, 70°C or higher and less than 150°C. The heating time when heating the region that will become the second region R2 is, for example, 1 minute or more and 360 minutes or less.
[0080] Next, the positive electrode current collector layer 21 and the positive electrode active material layer 25 are stacked to form the positive electrode layer 20 (positive electrode layer formation step S13). At this time, an insulating frame 26 is formed on the positive electrode layer 20 on the positive electrode current collector layer 21 in accordance with the design dimensions of the all-solid-state battery 1 after completion.
[0081] The grain growth step S12 may be performed after the cathode layer formation step S13.
[0082] Next, the positive electrode layer 20 and the solid electrolyte layer 30 are laminated (solid electrolyte layer placement step S14). In the solid electrolyte layer placement step S14, for example, the slurry constituting the solid electrolyte layer 30 is coated onto the positive electrode layer 20 under pressure using a transfer roller, and a transfer press is performed. At this time, the temperature is, for example, room temperature (for example, 10 to 35°C), and the pressure is, for example, 50 to 500 MPa.
[0083] Next, the positive electrode layer 20, on which the solid electrolyte layer 30 is laminated, is pressed (positive electrode pressing process S15). In the positive electrode pressing process S15, the positive electrode active material layer 25 and the positive electrode current collector layer 21 are pressed together. This positive electrode pressing process S15 increases the density of the positive electrode layer 20. In order to increase the density of the positive electrode layer 20, the temperature in the positive electrode pressing process S15 is, for example, 25 to 100°C, and the pressure is, for example, 800 to 1200 MPa.
[0084] The grain growth process S12 is preferably performed before the positive electrode pressing process S15.
[0085] Meanwhile, a negative electrode active material layer 15 is placed on the negative electrode current collector layer 11 to form a negative electrode layer 10 (negative electrode layer formation step S21). A negative electrode tab 14 is formed on the negative electrode current collector layer 11.
[0086] Next, the intermediate layer 40 is placed on the negative electrode active material layer 15 which is laminated on the negative electrode current collector layer 11 (intermediate layer placement step S22). In the intermediate layer placement step, for example, the intermediate layer 40 is coated onto the negative electrode active material layer 15 using a transfer roller while applying pressure, and a transfer press is performed. At this time, the temperature is, for example, room temperature (for example, 10 to 35°C), and the pressure is, for example, 50 to 800 MPa.
[0087] Then, the positive electrode layer 20, on which the solid electrolyte layer 30 is laminated, and the negative electrode layer 10, on which the intermediate layer 40 is laminated, are stacked together and pressed using a press (integration pressing process S31). This integrates the positive electrode layer 20, the negative electrode layer 10, the solid electrolyte layer 30, and the intermediate layer 40. In the integration pressing process S31, the positive electrode layer 20, the negative electrode layer 10, and the solid electrolyte layer 30 are stacked together and pressed. At this time, the temperature is, for example, 25 to 100°C, and the pressure is, for example, 500 to 900 MPa. Through the integration pressing process S31, the positive electrode side sheet member and the negative electrode side sheet member are integrated, and at the same time, the solid electrolyte layer 30 becomes denser.
[0088] Furthermore, the pressing pressure in the positive electrode pressing process S15 is greater than the pressing pressure in the integration pressing process S31.
[0089] Furthermore, the grain growth process S12 does not necessarily have to be performed before the positive electrode pressing process S15. However, it is preferable that the grain growth process S12 be performed at least before the integration pressing process S31.
[0090] Next, the formed laminate is cut with a rotary cutter (cutting step S32).
[0091] Next, although not shown in the diagram, the tips of multiple negative electrode tabs 14 are brought together and connected to the negative electrode tab lead 6. The tips of multiple positive electrode tabs 24 are brought together and connected to the negative electrode tab lead 6. Next, the laminate is covered with a resin that will form the outer casing 5. The tips of the positive electrode tab lead 7 and the tips of the negative electrode tab lead 6 are exposed from the outer casing 5, respectively.
[0092] Furthermore, the transfer of the solid electrolyte layer 30 to the positive electrode layer 20 in the solid electrolyte layer placement process S14, the pressing of the positive electrode layer 20 in the positive electrode pressing process S15, the lamination of the negative electrode layer 10 to the positive electrode layer 20 before integration, and the integration pressing in the integration pressing process S31 are performed on both sides of the positive electrode side sheet member. The transfer of the negative electrode active material layer 15 to the negative electrode current collector layer 11 in the negative electrode layer formation process S21 and the transfer of the intermediate layer 40 to the negative electrode layer 10 in the intermediate layer placement process S22 are performed on both sides of the negative electrode side sheet member. As a result, the all-solid-state battery 1 has a structure in which each layer is symmetrically laminated on both the upper and lower surfaces, as shown in Figures 1 to 3.
[0093] Based on the above, an all-solid-state battery 1 as shown in Figure 1 can be obtained.
[0094] The method for manufacturing the all-solid-state battery 1 according to this embodiment may include steps other than those described above. The method for manufacturing the all-solid-state battery is not limited to the method described above, and other known methods can be applied.
[0095] (Effects according to the embodiment) According to the above embodiment, the following effects can be obtained.
[0096] In the all-solid-state battery 1 of the above embodiment, the positive electrode current collector layer 21 is made of polycrystalline material. In the first region R1, which includes the boundary portion of the positive electrode tab 24 with the positive electrode current collector layer main body 22, the average particle size of the polycrystalline material is larger than the average particle size of the polycrystalline material of the positive electrode current collector layer main body 22. The average particle size of the polycrystalline material in the first region R1 is less than 3.0 μm.
[0097] Among the various parts of the positive electrode current collector layer 21, the region near the base of the positive electrode tab 24 is considered to be prone to fracture because it is easily affected by the expansion and contraction of the all-solid-state battery 1. With this configuration, by forming a first region R1, which is a region with a relatively large average particle size of polycrystalline material, in the region near the base of the positive electrode tab 24, the strength of the region near the base of the positive electrode tab 24 can be improved. Furthermore, by having an average particle size of polycrystalline material in the first region R1 of less than 3.0 μm, sufficient flexibility of the positive electrode tab 24 can be ensured. This makes it possible to suppress fracture of the positive electrode current collector layer 21. Therefore, an all-solid-state battery 1 with excellent durability can be provided.
[0098] Furthermore, if the average grain size of the polycrystalline material in the positive electrode current collector layer 21 increases, the electrical resistance in the positive electrode current collector layer 21 will increase, which may impair the battery performance of the all-solid-state battery 1. With this configuration, by reducing the average grain size of the polycrystalline material in the positive electrode current collector layer main body 22, the increase in electrical resistance in the positive electrode current collector layer main body 22 can be suppressed.
[0099] Furthermore, since the positive electrode current collector layer body 22 is laminated with the other layers, its strength is relatively less likely to be a problem. Therefore, it is possible to improve the durability of the all-solid-state battery 1 while ensuring its battery performance.
[0100] Furthermore, since the average grain size of the polycrystalline material in the first region R1 is less than 3.0 μm, the increase in electrical resistance in the first region R1 can be suppressed. This makes it possible to more effectively suppress the deterioration of the battery performance of the all-solid-state battery 1.
[0101] In the all-solid-state battery 1 of the above embodiment, the positive electrode current collector layer 21 is preferably made of at least one of aluminum and an aluminum alloy.
[0102] With this configuration, since aluminum particles are easily grown by heating, the first region R1 can be suitably formed by heating the positive electrode current collector layer 21.
[0103] Furthermore, because aluminum has excellent corrosion resistance, it is easier to ensure the durability of the positive electrode current collector layer 21 over a long period of time.
[0104] In the all-solid-state battery 1 of the above embodiment, it is preferable that the average grain size of the polycrystalline material in the second region R2 (second region R21 on the tab side), which is located on the opposite side (X+ direction side) from the positive electrode current collector layer main body portion 22 side to the first region R1 of the positive electrode tab 24, is smaller than the average grain size of the polycrystalline material in the first region R1.
[0105] Since the positive electrode tab 24 is joined to other positive electrode tabs 24 in a bent state, it is preferable that it be somewhat flexible. In particular, it is preferable that the region near the tip of the positive electrode tab 24 be flexible. On the other hand, if the average grain size of the polycrystalline material of the positive electrode tab 24 is increased, the positive electrode current collector layer 21 becomes rigid, which may cause the positive electrode tab 24 to buckle when the all-solid-state battery 1 expands. However, with this configuration, the flexibility of the positive electrode tab 24 can be easily ensured by reducing the average grain size of the polycrystalline material in the tab-side second region R21. In particular, it is easier to ensure flexibility near the tip of the positive electrode tab 24. This makes it possible to suppress buckling of the positive electrode current collector layer 21.
[0106] According to the all-solid-state battery 1 of the above embodiment, the end of the first region R1 opposite to the positive electrode current collector layer main body 22 side (X+ side) may be located closer to the positive electrode current collector layer main body 22 side (X- side) than the central part of the positive electrode tab 24 in the X direction.
[0107] With this configuration, the region in the positive electrode current collector layer 21 that is formed relatively hard can be extended further towards the tip, thereby effectively suppressing fracture of the positive electrode current collector layer 21. Furthermore, by adjusting the position in the X direction of the end of the first region R1 opposite to the positive electrode current collector layer main body 22, the balance between the effect of suppressing fracture of the positive electrode current collector layer 21 and the effect of suppressing buckling of the positive electrode current collector layer 21 can be adjusted.
[0108] In the all-solid-state battery 1 of the above embodiment, it is preferable that the average particle size of the polycrystalline material in the first region R is 0.5 μm or more and less than 3.0 μm.
[0109] With this configuration, by increasing the average grain size of the polycrystalline material in the first region to a certain extent, it is easier to ensure the strength of the first region, thereby suppressing buckling of the positive electrode tab. By decreasing the average grain size of the polycrystalline material within the first region to a certain extent, it is easier to ensure the flexibility of the first region, thereby suppressing fracture of the positive electrode tab. Therefore, the durability of the all-solid-state battery can be more effectively improved.
[0110] In the all-solid-state battery 1 of the above embodiment, the thickness of the positive electrode current collector layer 21 is preferably 0.005 mm or more and 0.05 mm or less.
[0111] If the thickness of the positive electrode current collector layer 21 is insufficient, the strength of the positive electrode current collector layer 21 will be inadequate. If the thickness of the positive electrode current collector layer 21 is excessive, excessive electrical resistance will occur in the positive electrode current collector layer 21. However, with this configuration, it is possible to more preferably improve the durability of the all-solid-state battery 1 while ensuring the battery performance of the all-solid-state battery 1.
[0112] In the all-solid-state battery 1 of the above embodiment, the positive electrode active material layer 25 preferably contains lithium nickel cobalt manganese composite oxide.
[0113] With this configuration, the thermal durability of the positive electrode active material layer 25 can be improved, making it easier to heat the positive electrode current collector layer 21 and the positive electrode active material layer 25 simultaneously.
[0114] Furthermore, the positive electrode active material layer 25 can contract during charging of the all-solid-state battery 1. This suppresses the expansion of the all-solid-state battery 1 during charging, thereby suppressing the rupture of the positive electrode current collector layer 21.
[0115] According to the manufacturing method of the all-solid-state battery 1 of the above embodiment, the manufacturing method of the all-solid-state battery 1 includes a grain growth step S12 in which a polycrystalline positive electrode current collector layer raw material is prepared, which has a positive electrode current collector layer main body portion 22 on which a positive electrode active material layer 25 is arranged and a positive electrode tab 24 extending from the positive electrode current collector layer main body portion 22, and the boundary portion of the positive electrode tab 24 with the positive electrode current collector layer main body portion 22 is heated to form a first region R1 in which the average grain size of the polycrystalline material is larger than the average grain size of the polycrystalline material of the positive electrode current collector layer main body portion 22.
[0116] By heating the positive electrode current collector layer 21, crystalline particles G that form the polycrystalline structure of the positive electrode current collector layer 21 can be grown. According to this manufacturing method, by performing the grain growth step S12, crystalline particles G that form the polycrystalline structure can be grown in the region near the boundary between the positive electrode tab 24 and the main body portion 22 of the positive electrode current collector layer, thereby forming a first region R1 in the positive electrode current collector layer 21.
[0117] According to the above embodiment, the manufacturing method of the all-solid-state battery 1 includes an integration pressing step S31 in which a positive electrode layer 20, a negative electrode layer 10, and a solid electrolyte layer 30 are stacked and pressed together. The grain growth step S12 is preferably performed before the integration pressing step S31.
[0118] When the positive electrode current collector layer 21 is pressed, it becomes difficult for the crystal particles G within the positive electrode current collector layer 21 to grow. However, with this manufacturing method, the crystal particles G within the positive electrode current collector layer 21 can be grown suitably, making it easier to create a difference between the average particle size of the polycrystalline material in the first region R1 and the average particle size of the polycrystalline material in the region of the positive electrode current collector layer 21 excluding the first region R1 (i.e., the second region R2).
[0119] According to the above embodiment, the manufacturing method of the all-solid-state battery 1 includes a positive electrode pressing step S15 in which a positive electrode active material layer 25 and a positive electrode current collector layer 21 are stacked and pressed together. It is more preferable that the grain growth step S12 is performed before the positive electrode pressing step S15.
[0120] According to this manufacturing method, the crystalline particles G within the positive electrode current collector layer 21 can be grown more favorably, making it easier to differentiate between the average particle size of the polycrystalline material in the first region R1 and the average particle size of the polycrystalline material in the region of the positive electrode current collector layer 21 excluding the first region R1 (i.e., the second region R2).
[0121] The present invention is not limited to the configuration of the above embodiments, and can be modified and applied as appropriate without altering the essence of the invention. Furthermore, a combination of two or more of the desirable configurations described in the above embodiments also constitutes the present invention. [Examples]
[0122] 1. Manufacturing of all-solid-state batteries <Example 1> (Fabrication of the positive electrode layer) As the positive electrode current collector, an aluminum foil measuring 500 m in length, 700 mm in width, and 12.5 μm in thickness (average particle size of polycrystalline material: approximately 0.4 μm) was prepared. The portion of the positive electrode current collector where the positive electrode active material layer and the insulating frame were not laminated was cut to form a tab measuring 35 mm in length and 50 mm in width. (See H122-4942-JP01 and H122-4942)
[0123] Next, the resulting tabs were heated at a temperature of 400°C for a heating time of 2 minutes.
[0124] A mixture was prepared by combining 80 parts by mass of lithium nickel cobalt manganese composite oxide (NCM622) as the positive electrode active material, 17 parts by mass of argyrodite-type sulfide solid electrolyte as the solid electrolyte material, 2 parts by mass of carbon black as a conductive additive, and 1 part by mass of SBR (styrene-butadiene rubber) binder as a binder. The resulting mixture was dispersed in 43 parts by mass of butyl butyrate to prepare a positive electrode active material layer slurry. The obtained positive electrode active material layer slurry was applied to both sides of the positive electrode current collector, with a dry basis weight of 27 mg / cm². 2 The surface was coated using a bar coater and dried to achieve a length of 520 mm, a width of 90 mm, a thickness of 80 μm, and a density of 3.50 g / cm³. 3 A positive electrode active material layer was formed.
[0125] Next, an insulating frame measuring 530 mm in length, 103 mm in width, and 78 μm in thickness was formed on the outer periphery of the positive electrode active material layer by intermittent coating. In this way, the positive electrode layer was fabricated.
[0126] (Preparation of solid electrolyte layer transfer sheet) A dispersion of argyrodite-type sulfide solid electrolyte (median diameter: 3.0 μm) was applied to a support sheet and dried to form an argyrodite-type sulfide solid electrolyte layer, thereby creating a solid electrolyte layer transfer sheet.
[0127] (Fabrication of the negative electrode layer) A 10 μm thick copper foil was prepared as the negative electrode current collector. The portion of the negative electrode current collector where the negative electrode active material layer and the intermediate layer were not laminated was cut to form a tab 35 mm long and 50 mm wide. A 7 μm thick metallic lithium foil was laminated onto the surface of the copper foil to create the negative electrode layer.
[0128] (Preparation of the intermediate layer transfer sheet) A total of 95 parts by mass of Sn particles (median diameter: 0.07 μm) as metal nanoparticles and acetylene black (median diameter: 0.05 μm) as amorphous carbon were mixed with 5 parts by mass of a PVDF-based binder as a binder. The resulting mixture was dispersed in 1000 parts by mass of NMP (N-methyl-2-pyrrolidone) to prepare an intermediate layer slurry. The resulting intermediate layer slurry was applied to a support sheet and dried to prepare an intermediate layer transfer sheet with a final thickness of 5 μm.
[0129] (Fabrication of all-solid-state batteries) A solid electrolyte layer of a solid electrolyte layer transfer sheet was placed on the positive electrode active material layer of the positive electrode layer. Then, the positive electrode layer and the solid electrolyte layer transfer sheet were press-bonded at a bonding pressure of 50 MPa. After that, the support sheet of the solid electrolyte layer transfer sheet was peeled off to create a solid electrolyte layer-positive electrode layer laminate. The intermediate layer of an intermediate layer transfer sheet was transferred onto the metallic lithium foil of the negative electrode layer. Then, the negative electrode layer and the intermediate layer were press-bonded at a bonding pressure of 300 MPa to create an intermediate layer-negative electrode layer laminate. The solid electrolyte layer-positive electrode layer laminate and the intermediate layer-negative electrode layer laminate were stacked alternately. The laminates of the solid electrolyte layer-positive electrode layer laminate and the intermediate layer-negative electrode layer laminate were press-bonded at a bonding pressure of 500 MPa to create a positive electrode layer-solid electrolyte layer-intermediate layer-negative electrode layer laminate. The positive electrode layer-solid electrolyte layer-intermediate layer-negative electrode layer laminate was cut to predetermined dimensions to obtain a laminate that forms one all-solid-state battery. The resulting laminate was housed in an outer casing, the tab portion of the positive electrode layer was connected to the positive electrode tab lead, and the tab portion of the negative electrode layer was connected to the positive electrode tab lead. The outer casing was then sealed to obtain an all-solid-state battery.
[0130] <Comparative Example 1> A solid-state battery was fabricated in the same manner as in Example 1, except that the temperature for heating the tab was set to 95°C.
[0131] <Comparative Example 2> An all-solid-state battery was fabricated in the same manner as in Example 1, except that the heating conditions for the tab were set to 550°C.
[0132] 2. Evaluation [Measurement of average grain size of polycrystalline material] The average particle size of the polycrystalline material in the first region of the positive electrode tab (sometimes simply referred to as "average particle size in the first region") was measured for each solid-state battery. The average particle size in the first region was measured by disassembling the solid-state battery to expose the positive electrode current collector layer and observing the first region with a scanning electron microscope (SEM). For each example and comparative example, the average particle size in the first region was measured for 60 solid-state batteries. For each example and comparative example, the range of the average particle size in the first region was confirmed.
[0133] [Capacity retention rate measurement] Using the all-solid-state batteries prepared in Example 1 and Comparative Examples 1 and 2, a cycle test was performed in which charge and discharge were repeated at a maximum charge voltage of 4.2V, a minimum discharge voltage of 2.5V, and a C rate of 0.1C, and the capacity retention rate after 500 cycles was measured. For each example and comparative example, if the capacity retention rate was less than 90%, it was evaluated as "poor," and if the capacity retention rate was 90% or more, it was evaluated as "good."
[0134] [Observation of the positive electrode tab's condition] In the all-solid-state batteries after the cycle test described above, cross-sectional observation using CT was performed to observe the condition of the positive electrode tabs. The presence or absence of buckling (also called tab breakage) and fracture of the positive electrode tabs were evaluated.
[0135] If the area of the positive electrode current collector, including the positive electrode tab, was bent into a Z-shape, it was classified as "buckling present." If zero solid-state batteries out of 60 showed buckling, it was evaluated as "good," and if one or more showed buckling, it was evaluated as "poor."
[0136] If a break or crack occurred at the boundary between the positive electrode tab and the main body of the positive electrode current collector layer, it was classified as "broken." If zero all-solid-state batteries out of 60 were found to be broken, it was evaluated as "good," and if one or more were found to be broken, it was evaluated as "bad."
[0137] [comprehensive evaluation] A product was rated "Good" if the evaluations for volume retention, buckling, and fracture were all "Good." A product was rated "Poor" if at least one of the evaluations for volume retention, buckling, or fracture was "Poor."
[0138] 3.Measurement results Table 1 shows, for each comparative example and each example, the range of average particle size (μm) of the polycrystalline material in the first region of the positive electrode tab, the capacity retention rate (%) and evaluation of the capacity retention rate, the number of all-solid-state batteries determined to have buckling and the evaluation of whether or not buckling occurred, the number of all-solid-state batteries determined to have fracture and the evaluation of whether or not fracture occurred, and the overall evaluation.
[0139] [Table 1]
[0140] The results in Table 1 show that the all-solid-state battery obtained in Example 1 exhibited good capacity retention even after repeated charging and discharging, and was less prone to buckling or fracture of the positive electrode tab. In contrast, the all-solid-state battery obtained in Comparative Example 1, which had a relatively small average particle size of polycrystalline material in the first region of the positive electrode tab, showed a low capacity retention rate and was prone to buckling of the positive electrode tab after repeated charging and discharging. The all-solid-state battery obtained in Comparative Example 2, which had a relatively large average particle size of polycrystalline material in the first region of the positive electrode tab, showed less buckling of the positive electrode tab after repeated charging and discharging, but had a low capacity retention rate and was prone to fracture of the positive electrode tab.
[0141] Furthermore, in Example 1, the average particle size of the polycrystalline material in the main body portion of the positive electrode current collector layer (second region on the main body side) was 0.2 μm or more and less than 0.5 μm. In Example 1, the average particle size of the polycrystalline material in the first region was larger than the average particle size of the polycrystalline material in the main body portion of the positive electrode current collector layer. Therefore, Comparative Example 3 was prepared as a comparative example in which the average particle size of the polycrystalline material in the first region and the average particle size of the polycrystalline material in the main body portion of the positive electrode current collector layer were made equal. For Comparative Example 3, the capacity retention rate measurement described above and subsequent observation of the positive electrode tab were performed.
[0142] In Comparative Example 3, an all-solid-state battery was fabricated in the same manner as in Example 1, except that the positive electrode current collector layer was heated at a temperature of 400°C for a heating time of 2 minutes.
[0143] In Comparative Example 3, the average particle size of the polycrystalline material in the first region and the average particle size of the polycrystalline material in the main body of the positive electrode current collector layer were both between 0.2 μm and 3.0 μm. In Comparative Example 3, the capacity retention rate after 500 cycles was 50%, which was a poor result. Buckling occurred in Comparative Example 3.
[0144] A comparison of Example 1 and Comparative Example 3 shows that when the average grain size of the polycrystalline material in the first region is larger than the average grain size of the polycrystalline material in the main body of the positive electrode current collector layer, the capacity retention rate is good and buckling of the positive electrode tab is less likely to occur. [Explanation of Symbols]
[0145] 1: All-solid-state battery, 20: positive electrode layer, 21: positive electrode current collector layer, 24: positive electrode tab, 25: positive electrode active material layer, 30: solid electrolyte layer, G: crystalline grains (polycrystalline), R1: first region, R2: second region, S12: grain growth process, S15: positive electrode pressing process, S31: integration pressing process.
Claims
1. An all-solid-state battery in which a negative electrode layer and a positive electrode layer having a positive electrode active material layer and a positive electrode current collector layer are stacked via a solid electrolyte layer, If we define the stacking direction as the stacking direction, and one of the directions perpendicular to the stacking direction as the first direction, The positive electrode current collector layer comprises a positive electrode current collector layer body portion that overlaps the positive electrode active material layer in the stacking direction, and a positive electrode tab extending from the positive electrode current collector layer body portion to one side in the first direction. The positive electrode current collector layer is a polycrystalline material, The first region, including the boundary between the positive electrode tab and the positive electrode current collector layer main body, has an average particle size of the polycrystalline material that is larger than the average particle size of the polycrystalline material in the positive electrode current collector layer main body. An all-solid-state battery in which the average particle size of the polycrystalline material in the first region is less than 3.0 μm.
2. The all-solid-state battery according to claim 1, wherein the positive electrode current collector layer is made of at least one of aluminum and an aluminum alloy.
3. The all-solid-state battery according to claim 1, wherein the second region of the positive electrode tab, which is located on the side of the positive electrode current collector layer body that is opposite to the first region, has an average particle size of the polycrystalline material that is smaller than the average particle size of the polycrystalline material in the first region.
4. The all-solid-state battery according to claim 1, wherein the end of the first region opposite to the positive electrode current collector layer body is located closer to the positive electrode current collector layer body than the central portion of the positive electrode tab in the first direction.
5. The all-solid-state battery according to claim 1, wherein the average particle size of the polycrystalline material in the first region is 0.5 μm or more and less than 3.0 μm.
6. The all-solid-state battery according to claim 1, wherein the thickness of the positive electrode current collector layer is 0.005 mm or more and 0.05 mm or less.
7. The all-solid-state battery according to claim 1, wherein the positive electrode active material layer comprises a lithium nickel cobalt manganese composite oxide.
8. A method for manufacturing an all-solid-state battery according to claim 1, A method for manufacturing an all-solid-state battery, comprising: preparing a positive electrode current collector layer raw material which is a polycrystalline material having a positive electrode current collector layer main body portion on which the positive electrode active material layer is arranged, and a positive electrode tab extending from the positive electrode current collector layer main body portion; and a grain growth step in which the boundary portion of the positive electrode tab with the positive electrode current collector layer main body portion is heated to form a first region in which the average particle size of the polycrystalline material is larger than the average particle size of the polycrystalline material in the positive electrode current collector layer main body portion.
9. The process includes an integrated pressing step in which the positive electrode layer, the negative electrode layer, and the solid electrolyte layer are stacked and pressed together. The method for manufacturing an all-solid-state battery according to claim 8, wherein the grain growth step is performed before the integration pressing step.
10. The positive electrode pressing process includes a step of overlapping and pressing the positive electrode active material layer and the positive electrode current collector layer. The method for manufacturing an all-solid-state battery according to claim 9, wherein the grain growth step is performed before the positive electrode pressing step.
Citation Information
Patent Citations
All-solid battery
JP2022104116A